Muslim Taxpayer's Preference: Paying Tax or Zakat? - Rahmawati Rahmawati; Nurul Rifani (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2023)
This research investigates the preferences of Muslim taxpayers between paying zakat or taxes. 119 Muslim taxpayers were recruited for online and offline survey studies. Factor analysis determines factors influencing Muslim taxpayer preferences between paying zakat or taxes. This study shows that Muslim taxpayers preferred to pay zakat rather than taxes. The faith factor has influenced Muslim taxpayers' preferences to pay zakat compared to paying taxes. Other factors include the level of compliance with obligations, the service quality factor for zakat management, the zakat knowledge level factor, the tax knowledge level factor, the religious practice factor, the Tax Services office service quality factor, and the tax benefit factor. From these results, it is expected that the government should evaluate tax policy that previously treated zakat only as deductible income to become a tax credit.JEL Classification: F6, Q49, R2How to Cite:Rahmawati, R., & Rifani, N. (2023). Muslim Taxpayer’s Preference: Paying Tax or Zakat. Signifikan: Jurnal Ilmu Ekonomi, 12(1), 207-220. https://doi.org/10.15408/sjie.12ii1.31555.